2021
DOI: 10.1186/s12909-021-03053-4
|View full text |Cite|
|
Sign up to set email alerts
|

Medical students’ perceptions and coping strategies during the first wave of the COVID-19 pandemic: studies, clinical implication, and professional identity

Abstract: Background The unfolding of the COVID-19 pandemic during spring 2020 has disrupted medical education worldwide. The University of Geneva decided to shift on-site classwork to online learning; many exams were transformed from summative to formative evaluations and most clinical activities were suspended. We aimed to investigate the perceived impact of those adaptations by the students at the Faculty of Medicine. Methods We sent an online self-admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 32 publications
(20 reference statements)
1
21
0
1
Order By: Relevance
“…The results indicated that the level of psychological destruction and quality of life caused by the COVID-19 pandemic on academic motivation was minimal. It can be said that, in cases of involvement and well-being, medical students did the best, which is also confirmed by the results of research conducted in other countries, perhaps due to professional identification or greater medical knowledge [ 41 ], Zilinskas et al [ 42 ] examined the mental health of higher education students (in different study fields) (N-1001) during COVID-19. The results indicate that the respondents highlighted anxiety and suicidality as mental health issues among higher education students in Lithuania during the COVID-19 pandemic.…”
Section: Methodsmentioning
confidence: 76%
“…The results indicated that the level of psychological destruction and quality of life caused by the COVID-19 pandemic on academic motivation was minimal. It can be said that, in cases of involvement and well-being, medical students did the best, which is also confirmed by the results of research conducted in other countries, perhaps due to professional identification or greater medical knowledge [ 41 ], Zilinskas et al [ 42 ] examined the mental health of higher education students (in different study fields) (N-1001) during COVID-19. The results indicate that the respondents highlighted anxiety and suicidality as mental health issues among higher education students in Lithuania during the COVID-19 pandemic.…”
Section: Methodsmentioning
confidence: 76%
“…Most (27/31) of the studies identified in our final list of included studies were primarily cross-sectional studies surveys without a control group. There was however one qualitative study [14], one mixed methods study [15], one qualitative study of photographic reflections taken during the pandemic [16] and one study that involved a pre and post pandemic survey (therefore a "control group") [17]. In the last study [17], data had been initially collected before lockdown in December 2019 and January 2020 and again after the end of lockdown in June 2020.…”
Section: Resultsmentioning
confidence: 99%
“…The potential stressors in this study were adapted from the Source of Stress Questionnaire. Wurth (2021) [15] Switzerland. Mixed methods.…”
Section: Perceived Stress Scale (Pss-10)mentioning
confidence: 99%
“…Dentre todos os fatores estudados, o apoio do professor apresentou efeito direto na autopercepção das competências educacionais dos alunos, enquanto que o estado emocional foi diretamente afetado pelo apoio dos colegas, o que demonstra a importância de um trabalho conjunto e harmônico entre a equipe da instituição de educação em saúde.Uma preocupação frequente de estudantes ao redor de todo mundo é com relação ao impacto que a pandemia trará para a formação dos futuros profissionais da saúde. Um estudo realizado porWurth et al (2021) avaliou a percepção do Outro estudo que também corrobora para a ideia de que o ensino remoto trouxe vantagens para o processo de aprendizagem ocorreu na Romênia, na Universidade de "Vasile Alecsandri" de Bacau Radu et al (2020). realizaram um estudo em que avaliou-se os impactos da pandemia frente ao processo de ensino-aprendizagem em plataformas on-line.…”
unclassified